Criminal justice and abnormals at the end of the 19th century in Belgium: Sources and principles of a social defence system - Cartuyvels, Yves (GLOSSAE. European Journal of Legal History, 2023)
The late 19th century was characterized in Belgium by the emergence of a new discourse of truth on crime and criminal that emphasized the threat posed by the ‘dangerous individual’ to society as a whole. The insane criminal, associated with abnormality and dangerousness, was rapidly considered as one of the categories to be controlled. As early as 1930, a social defence law created a special internment regime for these lunatics who escaped criminal punishment due to their mental deficiency. Recidivists, who were closely associated with the ‘abnormals’, were targeted by the same text. In both cases, the regime introduced in 1930 reflects the influence of the social defence doctrine, which, under the influence of Adolphe Prins, sought an eclectic compromise between the classical school principles and the new penology of positivistic obedience.